Peningkatan Identitas Visual (Branding) Produk Tempe Sagu untuk Peningkatan Nilai Jual UMKM di Desa Jebeng, Kecamatan Slahung, Kabupaten Ponorogo - Mustofa, Idam; Maradova, Akbar; Rahman Bahdar, Khairul Arief; Fauzan Abrori, Abdillah Malik; Saputra, Rifqi Auliya; Laksanadi, Rafly Faizal; Zidan Johnderose, Ahmad Qolbi; Chairunnas, Muhammad; Prestia, Syaipul Abdi; Wiyastono, Rafli Hibban; Taqwa, Ussisa 'Alat (Universitas Pahlawan Tuanku Tambusai, 2025)
UMKM contribute significantly to job creation, local economic growth, and improving community welfare. However, in the era of globalization and digitalization, MSMEs face major challenges to remain competitive. The objectives of this study are to determine the production process of sago tempeh, to determine the form and stages of digitalization of sago tempeh products. This research method uses the Participatory Action Research (PAR) method, which is a method of raising public awareness of the potential and problems that exist and encouraging community participation. The results of this study are the process of making sago tempeh from the beginning when it is still in the form of soybeans takes 4 days, for fermentation until it becomes sago tempeh ready to be sold. The digitalization efforts of the KKN Team for this sago tempeh production house are grouped into 3 stages: First, repekaching, Second, rebranding the product through social media, and Third marketing through e-commerce platforms. Sales results after digitalization have increased by around 40% from before. Many new consumers from the market place and additional followers on Instagram.